Failure of early postnatal dexamethasone to prevent chronic lung disease in infants with respiratory distress syndrome. Issue 1 (January 1996) - Shinwell, E. S.; Karplus, M.; Zmora, E.; Reich, D.; Rothschild, A.; Blazer, S.; Bader, D.; Yurman, S.; Dolfin, T.; Kuint, J.; Milbauer, B.; Kohelet, D.; et al.
Abstract : OBJECTIVE: To study the effect of early postnatal dexamethasone (days 1-3) on the incidence and severity of chronic lung disease in preterm infants with respiratory distress syndrome. METHODS: A multicentre, randomised, placebo controlled, blinded study was carried out in 18 neonatal intensive care units in Israel. The primary outcome measure was survival to discharge without requirement for supplemental oxygen therapy beyond 28 days of life. The secondary outcome measures were requirement for mechanical ventilation at 3 and 7 days, duration of ventilation or oxygen therapy, need for subsequent steroids for established chronic lung disease and incidence of major morbidities. RESULTS: The study consisted of 248 infants (dexamethasone n = 132; placebo n = 116). No differences were found in the outcome variables except for a reduction in requirement for mechanical ventilation at age 3 days in treated infants (dexamethasone 44%, placebo 67%; P = 0.001). Gastrointestinal haemorrhage, hypertension, and hyperglycaemia were more common in treated infants, but no life threatening complications, such as gastrointestinal perforation, were encountered. CONCLUSIONS: These data do no support the routine use of early postnatal steroids, but may justify further study in a selected, high risk group of infants.